(untitled) (Journal of EAHIL, 2017)
Dear Colleagues, Services provided by librarians to clinicians have been shown to be effective in saving time for health professionals and providing relevant information for decision-making. Patients’ length of stay was reduced when clinicians requested literature searches related to a patient’s case (L. Perrier et al., J Am Med Inform Assoc. 2014 May 28). Moreover, librarians have become more involved in developing high quality systematic reviews (P. Cruse and S. Protzko. Med Ref Serv Q. 2014;33:327). A study compared Wikipedia articles on the most costly medical conditions with standard, evidence-based, peerreviewed sources. The conclusion is that caution should be used when using Wikipedia to answer questions regarding patient care (R.T. Hasty et al. J Am Osteopath Assoc. 2014;14:368).